An overview of contract documents for building information modelling (BIM) construction projects - Ahmad Huzaimi, Abd Jamil; Mohamad Syazli, Fathi (Akademia Baru, 2017)
Building Information Modelling (BIM) enables close collaboration among project stakeholders to visualize what is to be built in a simulated environment by identifying any potential design, construction or operational issues. Despite the fact of its welldocumented benefits, the extensive integration of BIM throughout the project lifecycle remains sporadic. The conventional contracts used in the Malaysian construction industry were established before the development of BIM. As BIM becoming ingrain in the delivery process, the inadequacies of these existing contracts have become visible. This paper presents a review of recent studies through a procurement approach of BIM to establish the contractual context by addressing the commercial considerations and probable legal risks of professionals in Malaysia and other countries. This paper also outlines the reasons why the implementation of BIM will foster the evolution of integrated contract delivery methods.